Authority and Estrangement : An Essay on Self-Knowledge - Moran, Richard (Book collections on Project MUSE., 2011)
Since Socrates, and through Descartes to the present day, the problems of self-knowledge have been central to philosophy's understanding of itself. Today the idea of ''first-person authority''--the claim of a distinctive relation each person has toward his or her own mental life--has been challenged from a number of directions, to the point where many doubt the person bears any distinctive relation to his or her own mental life, let alone a privileged one. In Authority and Estrangement, Richard Moran argues for a reconception of the first-person and its claims. Indeed, he writes, a more thorou.